1981
DOI: 10.1113/expphysiol.1981.sp002590
|View full text |Cite
|
Sign up to set email alerts
|

Some Effects of Diet on the Mitotic Index and the Cell Cycle of the Ruminal Epithelium of Sheep

Abstract: SUMMARYThe mitotic index of the ruminal epithelium increased rapidly when the diet of sheep was chan ed from one based on roughage to a concentrate-based diet. After several days the mitotic index declined to a new level which was slightly higher than that observed initially.Autoradiography of sections ofrumen epithelium was used to construct percent labelled mitoses curv s, from which the duration of the phases of the cell cycle was determined. The duration of the cell cycle was about 24 hr but decreased to 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
75
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(84 citation statements)
references
References 13 publications
6
75
0
3
Order By: Relevance
“…The observed changes were most prominent in the AR and RV resulting in a marked 41% and 62% increase, respectively, in papillae surface in these rumen regions of h/c-fed sheep. A 57% to 95% elevation in rumen papillae size was also found in concentrate-fed sheep (Goodlad, 1981), goats (Shen et al, 2004) and bulls (Shen et al, 2005). Together with other factors, such as lower intraruminal pH values (Gaebel et al, 1987;Brossard et al, 2004) and increased blood flow (Dobson, 1984;Thorlacius, 1972), this strongly supported the passive absorption of non-dissociated SCFA by passive diffusion (Bugaut, 1987;Gaebel et al, 1987;Sehested et al, 2000).…”
Section: Morphology Of Ruminal Mucosamentioning
confidence: 49%
“…The observed changes were most prominent in the AR and RV resulting in a marked 41% and 62% increase, respectively, in papillae surface in these rumen regions of h/c-fed sheep. A 57% to 95% elevation in rumen papillae size was also found in concentrate-fed sheep (Goodlad, 1981), goats (Shen et al, 2004) and bulls (Shen et al, 2005). Together with other factors, such as lower intraruminal pH values (Gaebel et al, 1987;Brossard et al, 2004) and increased blood flow (Dobson, 1984;Thorlacius, 1972), this strongly supported the passive absorption of non-dissociated SCFA by passive diffusion (Bugaut, 1987;Gaebel et al, 1987;Sehested et al, 2000).…”
Section: Morphology Of Ruminal Mucosamentioning
confidence: 49%
“…Exclusively, after 6 wk of concentrate diet, ARP3 has been found to be upregulated at translational level, as validated by Western blot. One can speculate that ARP3 is involved in the well-known studied diet-dependent morphological alterations of the ruminal epithelium (18,26,54,55). Supporting this hypothesis, recently, gene ontology analysis after comparison of gene expression profiles in ruminal tissue from cows fed with low-or high-concentrate diets revealed that the regulation of the actin cytoskeleton is one of the most effected pathways (58).…”
Section: Discussionmentioning
confidence: 69%
“…The phenotypic effects of diets, particularly of concentrate supplementation on rumen morphology and physiology, have been well investigated (38, 55) and reviewed (7). In particular, feeding a diet containing highconcentrate rations increases the number and/or size of papillae in the rumen and influences the transport properties of the ruminal epithelium (19,26). Furthermore, a diet rich in concentrate increases short-chain fatty acid (SCFA) concentration and leads to a decrease of pH (47).…”
mentioning
confidence: 99%
“…Delving deeper into the molecular mechanisms behind this phenomenon, we can see that papillae proliferation remains the same, but cellular turnover increases (Goodlad, 1981). This results in an overall increase in cell number and thus papillae hyperplasia.…”
Section: Introductionmentioning
confidence: 88%